Towards a code of ethics for public services - Paranjpe, Nalini (1998)
The paper discusses the causes for the emergence of the contemporary debate on ethics in government and focusses on the inner or personal control as a strategy to guide the ethical behaviour of public officials. The Weberian rational - legal bureaucratic model does not take note of ethical issues contributing to several ethical dilemmas inherent in all human institutions. The reconstruction of morality in governance will proceed along four parameters - the individual, society, time and space. An attempt has been made to search for new directions to innovate strategies for the future in terms of ethical criteria reapplied to the new and often irreversible material and technical conditions which obtain today. The paper is an entreaty for rethinking the paradigm which has governed the society and politics of modern India since her Independence, particularly since it appears to have conspicuously failed in generating a respect for norms in the conduct of many aspects of public life. It discusses the moral dimension of the government in the context of the larger socio - cultural, political and economic issues and a broader value framework. - Reproduced
Keywords: Civil service - India; Civil service ethics - India; Civil service